Plaga de palomas - Erdrich, Louise; Higuera Glynne-Jones, Susana de la; Erdrich, Louise (Madrid : Ediciones Siruela, 2012)
The unsolved murder of a farm family haunts the small, white, off-reservation town of Pluto, North Dakota. The vengeance exacted for this crime and the subsequent distortions of truth transform the lives of Ojibwe living on the nearby reservation and shape the passions of both communities for the next generation.
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Indians of North America -- Fiction; Ojibwa Indians -- Fiction; North Dakota -- Fiction; Murder -- Fiction; Revenge -- Fiction; Electronic books